THE INFLUENCE OF BIODIESEL BLENDS (UP TO B-20) FOR PARTS OF DIESEL ENGINE FUEL SYSTEM BY IMMERSION TEST - Riesta Anggarani; Cahyo Setyo Wibowo; Emy Yuliarita (Scientific Contributions Oil and Gas, 2015)
The Government of Indonesia will implement the mandatory policy on the use of Diesel Fuel and Biodiesel mixture with minimum 20% volume of biodiesel (B-20) start from 2016. From technical point of view, compatibility issue becomes one of the problems to be considered by automotive industries. The concern relate with solvent characteristic of biodiesel, which cause the biodiesel and its blends react with the parts of fuel system, especially the elastomers. This work is aimed to identify the material constructed the fuel system parts, including metal and non-metal parts, which has good compatibility to biodiesel blends up to B-20. Identifi cation of the parts material was done by FTIR and DSC for non-metal parts and by XRD and XRF for metal parts. The immersion test is used to compare the effect of fi ve biodiesel-diesel fuel blends (B-0, B-5, B-10, B-15, and B-20) to the physical change of metal and non-metal parts of diesel fuel system in a 2500 hours test period. The physical change being checked is the weight of the parts. The result obtained that for immersed metal parts, the change of weight occurred in the range of 0.007% to 0.595%. The higher weight change obtained by non-metal parts in the range of 0.001% to 13.85%. The lowest change was shown by metal parts consists of an alloy of CuO, Al2O3 and SiO, whether for non-metal parts was shown by a polymer type of Fluoroviton A. Through FTIR analysis we also observed that fuels composition before and after immersed with the tested parts were not change signifi cantly means that effect of solvent characteristic of biodiesel in the fuel mixture is negligible.